Structural models predict marital commitment based on attachment styles and mediator variables self-control and early maladaptive schemas(in people with emotional extramarital relations) - saiedeh hadi; Hossein Eskandari; f s; عبدالله معتمدی; n f (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2016)
The main objective of this research religiosity structural model predictions based on attachment styles and marital commitment mediator variables self-control and early maladaptive schemas in people with emotional extramarital relations. Methods: This study was correlationalThe study population included all individuals who commit treason to have been married in the spring of 95 were referred to counseling centers in Tehran, where 242 people were selected using a hand. To collect the data, schema of the original Yang, adult attachment style Hazan and Shaver, Tanjy self-control, and commitment Adams and Jones were married. Data analysis and structural equation model using PLS-3 carried.The results showed that the tested model is of good quality. The direct effect of self-control and schema entitlements, accepting money (05 / 0p≤) and emotional deprivation (01 / 0p≤) on was significant.About the relationship between anxious attachment styles with marital commitment, self-control variables, and schemas of mistrust, abandonment, alienation and emotional deprivation played a mediating role. The relationship between avoidant attachment styles with marital commitment was only to mediate emotional deprivation schema.But what about the role of mediator did not have any secure attachment. Conclusion: Since marriage and choice of spouse is one of the most important decisions of life.In premarital counseling to measure and analyze the variables to be paid per couple.